Platycerium bifurcatum (Cav.) C.Chr. DI KEBUN RAYA PURWODADI - Solikin Solikin (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract-Platycerium bifurcatum is a fern which has potential as ornamental and medicinal plant. Study aimed to determine presence ofthis plant conducted in Purwodadi Botanic Garden using cruising method in 176 plots of plants collection in the gardens area. The results showed that Platycerium bifurcatum found growing spread on 28 plots and stick to the14 species, 14 genera and 12 family of host plants. Mostly it grow wildon some the host plants. The most dominant of the host is Albiziasaman (Jacq.) Merr. with relative frequency value was 59.155%. Keywords : Platycerium bifurcatum, ornamental plant, host, fern